Analisis Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan Kosmetik dan Perlengkapan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia 2018-2022 - Nova Fitrianti; Dwiyatmoko Puji Widodo; Yuni Siti Nuraeni (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of profitability and capital structure on the value of cosmetics and household equipment companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The research method uses a quantitative approach with multiple linear regression analysis. The research results show that neither profitability nor capital structure have a significant influence on company value. These findings indicate that other factors, such as product innovation, marketing strategy, and market perception, can be the main determinants in assessing company value in the cosmetics and household goods industry